2020
DOI: 10.3389/fnhum.2020.588494
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Human Interaction in the Virtual Age: A Perspective on the Future of fNIRS Hyperscanning

Abstract: Advances in video conferencing capabilities combined with dramatic socio-dynamic shifts brought about by COVID-19, have redefined the ways in which humans interact in modern society. From business meetings to medical exams, or from classroom instruction to yoga class, virtual interfacing has permeated nearly every aspect of our daily lives. A seemingly endless stream of technological advances combined with our newfound reliance on virtual interfacing makes it likely that humans will continue to use this modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 97 publications
(162 reference statements)
0
13
0
Order By: Relevance
“…However, clustering co‐occurrences of words and how they relate provided the possibility to predict the newest tendencies and the future of fNIRS. For example, in the last year, authors dedicated their attention to cognitive functions and motor impairment, 56,58,122,123 development and language, 124–127 social and emotional engagement, 128–130 BCI systems, 63,64 and rehabilitation 131 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clustering co‐occurrences of words and how they relate provided the possibility to predict the newest tendencies and the future of fNIRS. For example, in the last year, authors dedicated their attention to cognitive functions and motor impairment, 56,58,122,123 development and language, 124–127 social and emotional engagement, 128–130 BCI systems, 63,64 and rehabilitation 131 …”
Section: Discussionmentioning
confidence: 99%
“…For example, in the last year, authors dedicated their attention to cognitive functions and motor impairment, 56,58,122,123 development and language, [124][125][126][127] social and emotional engagement, [128][129][130] BCI systems, 63,64 and rehabilitation. 131 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers have assessed the occurrence of IBC during unstructured collaborative conversation tasks focused on joint problem-solving 54 , creative-innovation 55 or socio-emotional experiences during psychological counseling 56 . As highlighted in recent literature reviews 23,32,33,57 , analytic approaches have most commonly utilized task-averaging to assess mean levels of IBC at the region specific level. We refer to these analytical approaches as “averaged” in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging-based measures of cognitive effort may advance our understanding of the mechanistic effects of video conferencing technology on social interaction. Specifically, we propose that functional near-infrared spectroscopy (fNIRS) is a potentially informative tool to investigate neural and inter-brain differences between virtual and in-person interactions in a naturalistic setting 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have extended fNIRS measurements from single brain to hyperscanning applications to investigate shared brain functions related to social interactions in a laboratory [10], [11] and increasingly naturalistic settings [12]- [14]. We refer the reader to Balters et al [15] for a more comprehensive introduction to fNIRS hyperscanning. Results from fNIRS hyperscanning studies have shown increased inter-brain coherence to be related to enhanced levels of interaction between team members [10], [12]- [14], [16].…”
Section: Introductionmentioning
confidence: 99%